Morphology identification and molecular characterization of Lasiodiplodia theobromae causing fruit rot disease of guava (Psidium guajava L.) in Malaysia - Che Ludin, Rohaida (2017)
Guava (Psidium guajava L.) belongs to the family of Myrtaceae is native to tropical America. Postharvest diseases, which cause serious problems during storage and transportation of guava fruits, are the major factors that limit the thriving guava industry in Malaysia. The fruit rot diseases reduce the fruit quality by altering the consistency, colour, taste and reduce shelf-life. Fruit samples from guava peel showing brownish black lesions of irregular shape and rapid spread of internal decay may appear. Few studies have investigated fruit rot disease on guava, however, only morphological characteristics were used and no molecular characterization was conducted to identify the pathogen identification. The objectives of this study were 1) to identify primary pathogen that caused guava fruit rot based on morphological and cultural characters as well as analyses of nucleotide sequences of the internal transcribed spacer (ITS) region of ribosomal DNA 2) to construct ITS phylogeny based on ITS sequences and their closest relatives by using Maximum Likelihood method. In order to identify the fruit rot-causing agent, 10 symptomatic fruits were collected from Seri Kembangan Selangor farmers market and fungi were isolated from fruit samples. One species, which is Lasiodiplodia theobromae was isolated frequently from the infected guava fruit. Colony morphology, and growth rates of the representative isolates were determined from the single conidium isolate obtained from the guava fruits. The pathogen identity was compared based on amplified ITS sequence using Basic Logical Alignment Search Tool (BLAST) nucleotide searches at GenBank. The findings of this study confirmed the true identity of the pathogen associated with fruit rot disease of guava in Malaysia was 99% matched with BLASTn search and ITS sequence was from Lasiodipldia therobromae. Correct identification of this pathogen is helpful for more effective management of fruit rot disease of guava. Further screening of effective fungicides and understanding of the epidemiology of this fungal pathogen will help to reduce financial loss to the guava industry in Malaysia.